HUBUBNGAN ANTARA KOMUNIKASI INTERPERSONAL TERHADAP KEPUASAN PERKAWINAN PADA KELUARGA YANG HIDUP DI PEDESAAN - Yoshua Puguh Dellaroza; Ratriana Yuliastuti Endang Kusumiati (Media Bina Ilmiah, 2024)
Marital satisfaction is a subjective feeling perceived by married couples regarding thehappiness in their marriage, influenced by background factors and current circumstances. Interpersonal communication is an individual's ability to listen, understand others, express oneself, and the willingness to communicate honestly. This research aims to examine the relationship between interpersonal communication and marital satisfaction in rural families, utilizing a quantitative research method. Questionnaires were distributed through social media platforms to married families in Lempong Village, Karanganyar, Central Java. Data analysis involved statistical testsfor assumptions, correlation, and effective contribution. The research aimed to understand the relationship between interpersonal communication and marital satisfaction in families living in rural areas. The research findings revealed a correlation coefficient (r) of -0.421 with a significance value of 0.000 (p < 0.05), indicating a negative relationship between interpersonal communication and marital satisfaction in rural families. The effective contribution of interpersonal communication to marital satisfaction was 17.7%.